If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5x + 8 + 3x + 3x + -2 = 9 + 2.4 Reorder the terms: 6 + 8 + -2 + -5x + 3x + 3x = 9 + 2.4 Combine like terms: 6 + 8 = 14 14 + -2 + -5x + 3x + 3x = 9 + 2.4 Combine like terms: 14 + -2 = 12 12 + -5x + 3x + 3x = 9 + 2.4 Combine like terms: -5x + 3x = -2x 12 + -2x + 3x = 9 + 2.4 Combine like terms: -2x + 3x = 1x 12 + 1x = 9 + 2.4 Combine like terms: 9 + 2.4 = 11.4 12 + 1x = 11.4 Solving 12 + 1x = 11.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 1x = 11.4 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 11.4 + -12 1x = 11.4 + -12 Combine like terms: 11.4 + -12 = -0.6 1x = -0.6 Divide each side by '1'. x = -0.6 Simplifying x = -0.6
| K=37+273 | | 5p-14-8p=4 | | 2y-3=3y | | 2c^3+16c^2-18c=0 | | (x-3)=-2 | | 20x^3-20x=0 | | 4(6x+2)=56 | | 3x-4=4x-17 | | k^2-3k+5=0 | | 4y-7=2(y+1) | | F=1.8(37)+32 | | 5y-20=10 | | 12x^5+15x+9=0 | | -x^2+15x+54=0 | | K=10+273 | | 2x+6=-26-6x | | 4y-1=2y+2 | | X^2=3(5x+18) | | 5x+5-2x=29 | | 9+6x=x+59 | | (3x-2)(x-2)=4x-36 | | 20y-16=18-9 | | K=40+273 | | 4(3a-2)+3a=19 | | F=1.8(40)+32 | | 7x-10=114-6x | | 305=5x^3 | | K=30+273 | | -6+7x=x-12 | | 3(2x+5)=11-4x | | 6y(4y-3)+15y= | | 15x+5=80 |